Acyl-homoserine lactone-based quorum sensing in the Roseobacter clade: complex cell-to-cell communication controls multiple physiologies - Cude, William N.; Buchan, Alison (Frontiers in Microbiology, 2013)
Bacteria have been widely reported to use quorum sensing (QS) systems, which employ small diffusible metabolites to coordinate gene expression in a population density dependent manner. In Proteobacteria, the most commonly described QS signaling molecules are N-acyl-homoserine lactones (AHLs). Recent studies suggest that members of the abundant marine Roseobacter lineage possess AHL-based QS systems and are environmentally relevant models for relating QS to ecological success. As reviewed here, these studies suggest that the roles of QS in roseobacters are varied and complex. An analysis of the 43 publically available Roseobacter genomes shows conservation of QS protein sequences and overall gene topologies, providing support for the hypothesis that quorum sensing is a conserved and widespread trait in the clade.